Efficacy of Face-to-Face Delivered Cognitive Behavioral Therapy in Improving Health Status of Patients With Insomnia: A Meta-Analysis - Xu, Dawei; Cardell, Elizabeth; Broadley, Simon A.; Sun, Jing (Frontiers in Psychiatry, 2021)
Background: Face-to-face cognitive behavioral therapy (CBT) is one of the most widely used non-pharmacological treatment approaches for insomnia. The aim of this study is to assess the efficacy of face-to-face delivered CBT on health outcomes and to evaluate the effect of CBT components as subgroup variables to explain the efficacy of face-to-face delivered CBT on health outcomes in adults over 18 years old with insomnia. Methods: Relevant randomized controlled trial studies published in the past 22 years were searched through the electronic databases. The Physiotherapy Evidence Database (PEDro) scale was used to assess the quality of the 31 included studies. The mean difference and standard deviation of outcome variables and subgroup variables were analyzed using random effect model, and the heterogeneity among the articles was assessed with the Q-test and I2. Egger regression analysis was used to assess publication bias. Results: The meta-analysis showed a significant reduction in Insomnia Severity Index [standardized mean difference (SMD) = −2.56, 95% CI −3.81 to −1.30, p < 0.001], Pittsburgh Sleep Quality Index (SMD = −0.96, 95% CI −1.25 to −0.68, p < 0.001), sleep onset latency (SMD = −1.31, 95% CI −2.00 to −0.63, p < 0.001), wakening after sleep onset (SMD = −1.44, 95% CI −2.14 to −0.74, p < 0.001), number of awakenings (SMD = −1.18, 95% CI −2.10 to −0.26, p < 0.05), depression (SMD = −1.14, 95% CI −1.85 to −0.42, p < 0.01), and fatigue (SMD = −2.23, 95% CI −3.87 to −0.58, p < 0.01), and a significant increase in total sleep time (SMD = 0.63, 95% CI 0.28 to 0.98, p < 0.001), sleep efficiency (SMD = 1.61, 95% CI 0.92 to 2.29, p < 0.001), and physical health (SMD = 0.42, 95% CI 0.08 to 0.76, p < 0.05), in the CBT intervention group compared with the control group. There was no significant change in anxiety (SMD = −0.62, 95% CI −1.55 to 0.32, p > 0.05) and mental health (SMD = 1.09, 95% CI −0.59 to 2.77, p > 0.05) in CBT intervention group compared with control group. Group-delivered studies with larger number of intervention sessions and longer duration of single session provided a larger improvement in sleep quality. Conclusion: Face-to-face delivered CBT is effective in increasing total sleep time, sleep efficiency, and physical health, and reducing Insomnia Severity Index scores, Pittsburgh Sleep Quality Index scores, sleep onset latency, wakening after sleep onset, number of awakenings, depression, anxiety, and fatigue in patients with insomnia. Face-to-face delivered CBT is more effective when delivered through a larger number of sessions with longer duration of each session, and when delivered in groups. Face-to-face CBT is recommended to provide treatment to patients with insomnia in clinical settings. Systematic Review Registration:www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020200091, identifier: CRD4202020009.